Multifunctional Nanomaterials for Energy Applications - Simas Rackauskas; Federico Cesano; Mohammed Jasim Uddin (Nanomaterials, 2022)
In the last few decades, global energy requirements have grown exponentially, and increased demand is expected in the upcoming decades [...]